2008
DOI: 10.1002/gps.2050
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of effect of cognitive intervention programs for the community‐dwelling elderly with subjective memory complaints

Abstract: Both cognitive training and cognitive stimulation programs showed training effects and remained until 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 6 publications
2
27
0
6
Order By: Relevance
“…The present study demonstrates that while patients/caregivers and physicians both have reasonable facility in detecting the presence of a memory impairment, which is relatively consistent with previous findings (Schmand et al, 1996; Gron et al, 2002; Lautenschlager et al, 2005; Barnes et al, 2006; Cook et al, 2006; Mol et al, 2006; Glodzik-Sobanska et al, 2007; Clement et al, 2008; Minett et al, 2008; Snitz et al, 2008; Tsai et al, 2008), they do not have the same facility with word-finding/language deficits. This difficulty with word-finding/language assessments likely extends from a variety of reasons, including the lack of a clear definition of a word-finding/language impairment, a metric of these functions, and transparent criteria of significant impairments to this domain.…”
Section: Discussionsupporting
confidence: 91%
“…The present study demonstrates that while patients/caregivers and physicians both have reasonable facility in detecting the presence of a memory impairment, which is relatively consistent with previous findings (Schmand et al, 1996; Gron et al, 2002; Lautenschlager et al, 2005; Barnes et al, 2006; Cook et al, 2006; Mol et al, 2006; Glodzik-Sobanska et al, 2007; Clement et al, 2008; Minett et al, 2008; Snitz et al, 2008; Tsai et al, 2008), they do not have the same facility with word-finding/language deficits. This difficulty with word-finding/language assessments likely extends from a variety of reasons, including the lack of a clear definition of a word-finding/language impairment, a metric of these functions, and transparent criteria of significant impairments to this domain.…”
Section: Discussionsupporting
confidence: 91%
“…The resulting improvement in reality orientation via calligraphy treatment has been found to help elders by halting confusion, disorientation, social withdrawal, and apathy 19. This activity may help seniors to become more alert and sensitive to their environment, enabling them to remain cognitively fit for a longer period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Because mild cognitive impairment may lead to a sense of frustration, a lower level of life satisfaction, or even dementia,18 effective nonpharmacological interventions need to be found to optimize cognitive function in older people with mild cognitive impairment and to delay cognitive deterioration 19…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent meta-analysis (Gross et al, 2012), the effect sizes of memory interventions ranged from medium to large values, indicating positive results of memory interventions in optimizing the memory functioning of older adults. In addition, one study showed that older adults had improvements in verbal memory that lasted 6 months after learning mnemonic and problem-solving strategies compared to those in a no-treatment control condition (Tsai et al, 2008), suggesting the presence of a relatively long-lasting effect. Furthermore, some studies have found positive effects of memory interventions on improving older adults’ self-perception of memory capabilities and psychological wellness (Floyd and Scogin, 1997; Valentijn et al, 2005; Belleville et al, 2006).…”
Section: Introductionmentioning
confidence: 99%